Enantioselective total synthesis of (−)-α-kainic acid - Farwick, Andreas; Helmchen, Günter (Organic letters, 2010)
An enantioselective total synthesis of (−)-α-kainic acid is described. Key steps are an Ir-catalyzed allylic amination with a propargylic amine to provide an enyne and a diastereoselective intramolecular Pauson−Khand reaction. Subsequent steps involve a Baeyer−Villiger reaction, reduction of the resulting lactone, and direct Jones oxidation of a silyl ether.
Gesehen am 08.08.2023